Effects of a Single Cell Protein (Methylococcus capsulatus, Bath) in Pacific White Shrimp (Penaeus vannamei) Diet on Growth Performance, Survival Rate and Resistance to Vibrio parahaemolyticus, the Causative Agent of Acute Hepatopancreatic Necrosis Disease - Jintasataporn, Orapint; Chumkam, Srinoy; Triwutanon, Supawit; LeBlanc, Allan; Sawanboonchun, Jarin (Frontiers in Marine Science, 2021)
The efficacy of a single cell protein (SCP) methanotroph (Methylococcus capsulatus, Bath) bacteria meal (FeedKind®, Calysta, Menlo Park, CA, United States), in Pacific white shrimp (Penaeus vannamei) diets was studied to determine growth performance, survival rate and disease resistance against Vibrio parahaemolyticus causing Acute Hepatopancreatic Necrosis Disease (AHPND). The growth trial was assigned in a completely randomized design (CRD) with four treatments and 5 replicates of each, T1: a fishmeal-based control containing 15% fish meal and 3 diets with graded levels of methanotroph bacteria meal, namely T2: 5% methanotroph bacteria meal, T3: 10% methanotroph bacteria meal, and T4: 15% methanotroph bacteria meal. Shrimp were fed ad libitum for 6 weeks on trial diets to assess growth. Subsequent to the growth trial, three replicates of the same groups were exposed to V. parahaemolyticus by a single bath challenge and held for a further 15 days on the same diets as the growth study to assess survival and resistance. No significant differences (p > 0.05) in survival or in growth performance, including final weight, weight gain, specific growth rate, feed consumption or feed conversion ratio of white shrimp fed feeds containing methanotroph bacteria meal or control diets for 6 weeks. Immune markers such as hemocyte counts, phenoloxidase, superoxide dismutase and lysozyme activity were similar across all groups after the 6-week feeding trial. In a V. parahaemolyticus challenge, methanotroph bacteria meal in the diet significantly promoted the survival rate, and the reduction of Vibrio sp. in the hepatopancreas of white shrimp. Hemocyte count and phenoloxidase activity showed no significant differences (p > 0.05) between diet treatment groups, but hemolymph protein was significantly higher (p < 0.05) in shrimp fed diets containing 15% methanotroph bacteria meal after challenge. The Vibrio colony counts from hepatopancreas in the treatment groups were all significantly lower than the control (p < 0.05). The findings show that methanotroph bacteria meal can entirely replace fishmeal in white shrimp diets and the 15% inclusion of methanotroph bacteria meal in shrimp diet shows no adverse effects on growth performance, feed utilization and survival rate. In addition, shrimp fed methanotroph bacteria meal diets exhibited improved survival rates to an AHPND challenge.